"Conservación y viabilidad del ácido alfa-naftalenacético en el enraizamiento de estacas de cacao (Theobroma cacao L.) CCN-51 de origen trinitario" - Mora Zambrano, Jeniffer Lissbeth (2018)
Ecuador is one of the countries with the highest production of cocoa, and is an important source of the local economy. However, it is estimated that 405 of the current surface area requires renewal due to deterioration. For this reason, the methodology of rooting.